Mechanical Properties of Hardened High Strength Concrete. (2016) - Constantinescu, Horia; Gherman, Oana; Negrutiu, Camelia; Ioan, Sosa Pavel
Abstract: With the development of new and efficient admixtures for concrete, the production of high strength concrete (HSC) is becoming available at competitive prices. The behavior and properties of HSC are being studied around the world, but one of the advantages of concrete, namely that it can be cast using local materials, when dealing with new concretes can be a disadvantage, because research conducted elsewhere does not necessarily apply to the materials available near the construction site. The HSC studied in this research was cast using commercially available materials that require no special investments to procure. Samples were cast according to current standard provisions and tested at different ages in order to determine the mechanical properties of the produced concrete that are of interest to structural engineers and construction professionals. The samples were cured in different conditions in order to study the influence this has on the properties of the concrete. Results obtained show that some properties of high strength concrete are influenced by curing conditions, these properties are highlighted in the paper.